Harf Ma'ani's Distinction and Its Application in Arabic-Indonesian Translation - Sulthon Farhan Tsani; Ikhwanul Fitra Isman; Farrel Arfiko Ferdiansyah (LITTERATURA: Jurnal Bahasa dan Sastra, 2023)
This article explain the influence of "harf ma'āni" in producing meaning in Arabic. Through the study of nahwiyah dilaliyah, researchers will examine various forms of sentences in Arabic such as fi'il madzi, fi'il mudhāri’, masdar, isim fā’il and so on whose meaning can change from the lexical meaning (dictionary) due to the inclusion of the harf al-ma 'ani. This study is important to see the various meanings of Arabic sentences that are juxtaposed with harf al-ma'ani. The method used in this research is a qualitative method (qualitative research) with library research (library research). The primary data source for this research is a number of Arabic texts taken from a book entitled Dalīl fī al-Tarjamah by Dr. Rofi'i. While secondary sources for this research were taken from various scientific literature such as books, journal articles, dictionaries, and various other literature related to this research topic. This study concludes that the lexical meanings of the forms fi'il mādhi, fi'il mudhāri’, masdar, and isim fā’il can change and even contradict each other due to the inclusion of the harf ma’āni that follows them. Arabic language reviewers, especially Arabic-Indonesian translators, must be able and thorough in observing changes in the meaning of a sentence due to the inclusion of harf ma’āni which form new meanings and even contradict each other with their lexical meanings.